Body cell mass measured by bioelectrical impedance spectroscopy in professional football (soccer) players - Melchiorri, G.; Monteleone, G.; Andreoli, A.; Calla, C.; Sgroi, M.; de Lorenzo, A. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: The aim of this study was to measure body cell mass (BCM) in two football (soccer) teams and assess if there are differences in body composition among players of different field positions. Methods: Two professional Italian (male) football teams, representing two different divisions (A and C), have been recruited. There were 14 players (4 forwards, 4 defenders, 6 midfielders) in A and 18 players (4 forwards, 4 defenders, 8 midfielders, 2 goalkeepers) in C. Fat free mass (FFM), fat mass (FM), percent body fat (%BF), and BCM have been assessed using bioelectrical impedance spectroscopy (BIS). Results: There were no significant differences in age, body weight, height or body mass index between teams. Team A's BCM was approximately 4 kg greater than C (P=0.001). FFM was significantly greater in midfielders and defenders in A vs C (P=0.02). FFM was significantly lower in forwards compared to defenders within A (P=0.02). Within A, FM and %BF were significantly lower for defenders compared to forwards and midfielders (P=0.01), and BCM was significantly greater in forwards vs defenders (P=0.01), with no significant differences among other field positions. BCM was significantly greater in forwards vs midfielders and defenders within C (P=0.02), with no significant differences between midfielders and defenders. Conclusions: BCM, measured using BIS, represents an innovative, simple approach to assess body composition. The present study demonstrates that it is very important to analyze body composition in football players, not only with the aim to evaluate the variation of weight in a quantitative and qualitative way, but also with the purpose of selecting players for specific roles. Although these results must be considered not yet conclusive, they could be an important information for coaches, especially during the selection of young football players.